Multiscale graphene oxide–carbon fiber reinforcements for advanced polyurethane composites. (August 2016) - Jiang, Shuai; Li, Qifeng; Wang, Junwei; He, Zhenglong; Zhao, Yuhua; Kang, Maoqing
Graphical abstract: Abstract: Multiscale graphene oxide/carbon fiber (GO/CF) reinforcements were developed for polyurethane (PU) elastomer composites. GO was first coated on CF surface by electrophoretic deposition (EPD), aiming to improve the CF/PU interfacial adhesion. The EPD process improved the mechanical anchoring and chemical interaction between CFs and PU through increased surface roughness and oxygen content of CFs, thereby improved the CF/PU interfacial shear strength. The fibers were then mechanically mixed with GO to achieve a multiscale reinforcement. The strengthening of the matrix, especially the local stiffening of fiber/matrix interphase, is beneficial for the interfacial mechanical anchoring. The multiscale reinforcement resulted in an improvement of 46.4% in the tensile strength of PU elastomer. Compared with untreated-CF/PU, individual process of EPD treatment and mechanical mixing of GO resulted in an improvement of 16.9% and 13.9% of the strength, respectively. The enhanced reinforcing performance of GO-deposited CFs was attributed to the improved fiber–matrix interfacial adhesion.